Electrical half-wave rectification at ferroelectric domain walls. Issue 11 (November 2018) - Schaab, Jakob; Skjærvø, Sandra; Krohns, Stephan; Dai, Xiaoyu; Holtz, Megan; Cano, Andrés; Lilienblum, Martin; Yan, Zewu; Bourret, Edith; Muller, David; Fiebig, Manfred; Selbach, Sverre; et al.
Abstract Domain walls in ferroelectric semiconductors show promise as multifunctional two-dimensional elements for next-generation nanotechnology. Electric fields, for example, can control the direct-current resistance and reversibly switch between insulating and conductive domain-wall states, enabling elementary electronic devices such as gates and transistors. To facilitate electrical signal processing and transformation at the domain-wall level, however, an expansion into the realm of alternating-current technology is required. Here, we demonstrate diode-like alternating-to-direct current conversion based on neutral ferroelectric domain walls in ErMnO3 . By combining scanning probe and dielectric spectroscopy, we show that the rectification occurs at the tip–wall contact for frequencies at which the walls are effectively pinned. Using density functional theory, we attribute the responsible transport behaviour at the neutral walls to an accumulation of oxygen defects. The practical frequency regime and magnitude of the direct current output are controlled by the bulk conductivity, establishing electrode–wall junctions as versatile atomic-scale diodes. Electrode–domain wall junctions in ferroelectric ErMnO3 act as nanoscale diodes.